2021
DOI: 10.5001/omj.2021.18
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Trends in Iraq 2000–2016

Abstract: Objectives: Precise and quantitative assessment of the trend of cancer burden enables policymakers and health managers to prioritize diseases and allocate resources better. This infers what caused a decrease or increase in the rate of cancer occurrence, and if it denotes timing of implementation of a control measure, it presents the impact on the disease rate. This study’s objective was to evaluate trends in child and adult cancer in Iraq from 2000 onwards. Methods: We used the registries of the Iraqi Ministry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…All types of cancer were more common among men compared to women except for bone and brain cancer, which were more common among women. This was confirming in the findings of previous study that was conducted in Iraq, which concluded that most cancers were predominant in males [ 9 ]. Previous studies that examined the epidemiology of cancer and clinical characteristics of cancer patients were restricted to specific types of cancer or to ICU settings.…”
Section: Discussionsupporting
confidence: 92%
“…All types of cancer were more common among men compared to women except for bone and brain cancer, which were more common among women. This was confirming in the findings of previous study that was conducted in Iraq, which concluded that most cancers were predominant in males [ 9 ]. Previous studies that examined the epidemiology of cancer and clinical characteristics of cancer patients were restricted to specific types of cancer or to ICU settings.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, tumors in patients with Middle Eastern ancestry that had both a PTEN loss and ERG fusion had a higher risk of biochemical relapse when compared to the European population, where PTEN loss alone was associated with worse clinical outcome. These data confirm that the genomics of prostate cancer differs between men with Middle Eastern ancestry and those from East Asian, African, and European populations, which is likely reflective of factors leading to the higher incidence, rate of disease progression, and cause-specific mortality observed in other ancestries compared with men with Middle Eastern ancestry [30,31].…”
Section: Discussionsupporting
confidence: 64%
“…Cancer incidence rates for all cancer types increased in the KRG between 2013 and 2019, meanwhile in other parts of Iraq, the cancer rate increased from 44.58 to 67.86/100,000 between 2008 and 2016, representing a more than 50% increase (Hussain and Lafta, 2021). Although, these rates were lower compared to neighbouring countries, or countries in Europe, East Asia and the US (Yazdani-charati et al,2014), which is likely associated with the lack of implementing evidence-based cancer control programs and planning, which are fundamental for a high-quality cancer data registry, but which are almost totally unavailable (Ferlay et al, 2019) in most low-and middle-income countries, including in the KRG.…”
Section: Discussionmentioning
confidence: 98%